A Rare Case of Primary Intrapulmonary Neurilemmoma Diagnosed in a 43-Year-Old Asymptomatic Man with a Well-defined Intrapulmonary Mass - Chrysikos, Serafeim; Kaponi, Maria; Triantafillidou, Christina; Karampitsakos, Theodoros; Tzouvelekis, Argyrios; Anyfanti, Maria; Marossis, Konstantinos; Konstantinou, Marios; Tringidou, Rodoula; Bouros, Demosthenes; Dimakou, Katerina (Frontiers in Oncology, 2018)
Neurilemmoma, also termed schwannoma, presents as a well-circumscribed and encapsulated mass in the human body and is almost always solitary. CT scan of a patient with neurilemmoma shows a round, ovoid or lobulated well demarkated solid mass of soft tissue density. Primary intrathoracic neurogenic tumors can originate anywhere in the thorax, but are most frequently found in the posterior mediastinum in the costovertebral angle. Here we report a rare case of a 43-year-old man, previously healthy and never smoker, who presented with a mass adjacent to the right pulmonary hilum. This was an incidental finding on a chest x-ray after annual checkup at his workplace. The diagnosis was primary intrapulmonary neurilemmoma. Primary intrapulmonary neurilemmoma is an extremely rare tumor. However, based on the above, chest CT findings of a well-defined solid mass in an asymptomatic patient should raise the suspicion of neurilemmoma, irrespective of the tumor localization.